Political Buddhism, Islamic Orthodoxy and Open Economy: The Toxic Triad in Sinhalese–Muslim Relations in Sri Lanka. (June 2014) - Ali, Ameer
After nearly a millennium of uninterrupted harmony between the Sinhalese and Muslims in Sri Lanka, economic and ethno-religious developments after the 1970s have created an atmosphere of communal tension between the two groups. While a new wave of political Buddhism with its militant offshoot amongst the Sinhalese and the growth of a rigid Islamic orthodoxy amongst the Muslims have provided the ethno-religious dimension to this tension, the post-1977 open economy has added an economic dimension to it. The interplay of this toxic triad is a reminder of a similar scenario that produced the first Sinhalese-Muslim racial riots in the country in 1915. Unlike the first, which occurred in the colonial context, the current one, which if not arrested, will not only jeopardize Sinhalese–Muslim harmony but also will result in adverse consequences in Sri Lanka's relations with Muslim countries.